3d Printing in Medicine. (Woodhead Publishing series in biomaterials., 2017)
This book examines the emerging market of 3D-printed biomaterials and its clinical applications. It focuses on commercial and premarket tools, and looks at applications within medicine and the future outlook for the field. It includes the fundamentals of 3D printing, including topics such as materials, and hardware; 3D printing applications within medicine; and 3D printing in diagnostics and drug development and for disease models, plus 3D printers for surgical practice.